Relações entre Imperialismo estadunidense e luta armada na Ditadura Civil-Militar brasileira: o caso da Ação Libertadora Nacional - Palhares, Carolina de Castro (2020)
The purpose of this essay is to demonstrate how the Ação Libertadora Nacional (ALN) - National Liberation Action - analyzed and reacted to US imperialism during the 1964 coup d’état. Throughout the second half of the 20th century, South America was overcome by a wave of dictatorial regimes, which emerged to guarantee and preserve the subordination of the Southern Cone to the system of power hegemony established by the US in the context of the Cold War. In Brazil, in April 1964, a civil-military coup, strongly instigated and supported by the United States, established in the country a dictatorship that lasted more than twenty years, triggering an environment of internal conflict among the different layers of the population, with emphasis on the emergence of urban guerrillas. From this context, the aim is to reiterate the hypothesis that the National Liberation Action had internal and external purposes to fight for the liberation of the population from the bonds of the military and the US imperialism that was plaguing Brazil. Thus, through inductive and historical methods and documentary research, in which both documents produced by ALN militants found in the “Edgard Leuenroth Archive” as well as declassified official documents from the United States government, this thesis seeks to demonstrate that all the environment of repression that was installed, with US help, contributed to the radicalization of individuals who sought to transform and overcome the current system through the formation of urban guerrillas such as the Ação Libertadora Nacional.